The Impact of a Qualitative Research Interview on Workers’ Views of Their Situation - Butterfield, Lee D.; Borgen, William A.; Amundson, Norman E. (Canadian Journal of Counselling and Psychotherapy, 2009)
The purpose of this research was to explore whether qualitative research interviews impacted participants’ views of their situations. Forty-five workers who reported handling well changes that affected their work were interviewed to explore their experiences of change, factors that helped and hindered their ability to handle change, and assess the impact of the interview. Using a pretest/posttest design, participants rated their view of themselves in their situations on a scale from 0 to 10 at the beginning and then the end of a semi-structured interview. Statistical and practical significance were found, suggesting the research interviews had an impact. Research and ethical implications for researchers are discussed.